Analysis of ICT in the Strategic Modernisation Programme of the Paraguayan Supreme Court - Chamorro Ibarrola, Rosa Liz (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPA)--Stellenbosch University, 2012.